Dampak Perubahan Undang-Undang No. 36 Tahun 2008 terhadap Penerapan PPH Potong Pungut pada Perusahaan Jasa Cleaning Service (Studi Kasus pada PT. Jasa Mulia Iramandiri) - Rizki Ahmad Fauzi (STIE Binaniaga, 2010)
The introdution described about the history of income tax, the book observation concerning about the meaning of Tax and the chronological alteration of the Income Tax regulations. Research Method described the structure of PT. Jasamulia Iramandiri, along the literature using research data as a secondary data The comparison between the old Law on the new Act has some interesting differences to explore, also elucidate between Old law dan the New Law of Income Tax concerning PPh 21,23,and 25. This discussion are simulate the calculation of Income Tax Law chapter 21 in two version the old and newest Law, also the impact of the Law alteration to accounts on the financial statement.